MANAGEMENT OF ADRENO CORTICAL CARCINOMA: CASE REPORT - Duha, Diki Arma; Mirza, Hendy (Indonesian Urological Association, 2022)
Objective: Adreno cortical carcinoma (ACC) is a rare malignancy. Currently, surgical resection offers the best chance of cure with localized tumor. Multimodal therapy including systemic chemotherapy and radiation therapy are often required for locally advanced and metastatic disease aims to decrease these high recurrence rates. Case(s) presentation: A 42-year-old male patient was referred from internist due to mass in left adrenal. Solid mass with calcification on left adrenal gland within size 9 x 11.8 x 11.5 cm was found in MSCT. We performed complete surgical resection (adrenalectomy), and results from pathology anatomy was ACC functional T2N1M0 (stage 3). The patient was planned eight times chemotherapy with etoposide and carboplatin, but he decided to stop the treatment after six times due to no constitutional complaint. We found no residual mass on follow up six months after operation and patient demonstrated a good clinical outcome after one year. Discussion: We perform open adrenalectomy and after surgery mitotane plus etoposide, cisplatin, doxorubicin (EDP) administered as first-line therapy but we only did chemotherapy with etoposide and carboplatin because mitotane was not covered by patient insurance. We chose to not perform radiation therapy due to lesser benefit of adjuvant radiotherapy as evidenced by many studies in term of recurrence-free survival and overall survival. Conclusion: In our case, adreno cortical carcinoma treated with open adrenalectomy combined with 6 times chemotherapy used etoposide and carboplatin demonstrated a good clinical outcome after 1 year.